2018
DOI: 10.1038/s41390-018-0217-3
|View full text |Cite
|
Sign up to set email alerts
|

Early behavioral indices of inherited liability to autism

Abstract: Recent developmental studies have indicated that autism spectrum disorder (ASD) may arise from critical combinations of specific early neurobehavioral susceptibilities, each of which may be traceable to partially-independent sets of genetic variation. These susceptibilities and their respective genetic origins may not relate to the characterizing symptoms of ASD (after it develops) in a straightforward way. Furthermore, some of the contributory liabilities may not necessarily be specific to ASD, and may accoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 79 publications
(86 reference statements)
0
16
0
Order By: Relevance
“…The possibility of a parsimonious effect of sex-and therefore a convergent neural signature of its effect in modulating phenotypic expression of inherited liability-arises from the observation that, along the autism spectrum and across its many genetic causes, the symptom structure of the condition is unitary in nature. Thus, disparate symptoms might arise from shared neural mechanisms [80,81] that are uniquely vulnerable to disruption early in life-less among females, more among males-in individuals who inherit ASD susceptibility [5,82,83]. In the present study, we failed to replicate an array of specific brain responses that were reported to differentiate siblings of ASD probands from unrelated controls in prior research.…”
Section: Discussionmentioning
confidence: 56%
“…The possibility of a parsimonious effect of sex-and therefore a convergent neural signature of its effect in modulating phenotypic expression of inherited liability-arises from the observation that, along the autism spectrum and across its many genetic causes, the symptom structure of the condition is unitary in nature. Thus, disparate symptoms might arise from shared neural mechanisms [80,81] that are uniquely vulnerable to disruption early in life-less among females, more among males-in individuals who inherit ASD susceptibility [5,82,83]. In the present study, we failed to replicate an array of specific brain responses that were reported to differentiate siblings of ASD probands from unrelated controls in prior research.…”
Section: Discussionmentioning
confidence: 56%
“…If our findings on the relative non-heritability of severity ratings among clinically-affected cases are representative of most or all autistic syndromes, any observed relationships between biological markers and severity ratings would not be expected to relate to the cause of the condition, rather to modifiers or epiphenomena, and, therefore, should be interpreted cautiously. Moreover, these data underscore alternate prospects for biomarker discovery in which neural, genetic, and physiologic signatures are linked to endophenotypic contributors to autistic syndromes (see Pohl et al 2019;Constantino 2019) within the normal range of the population distribution.…”
Section: Discussionmentioning
confidence: 91%
“…Findings from the present report echo this work by demonstrating that it is ASD endophenotypes (language, adaptive behavior) and not ASD traits that are associated among concordant pairs. Taken together, this work emphasizes the importance of investigating the contribution of familial genetics to early precursor behavioral traits rather than to the diagnosis of ASD itself or to behaviors that emerge well after symptoms are evident [48].…”
Section: Discussionmentioning
confidence: 94%
“…There is growing support for the hypothesis that ASD, which is both polygenic [3][4][5] and pleiotropic [45,46] in nature, may be traceable to early-emerging developmental endophenotypes that are both specific and nonspecific to ASD [47,48]. This is evidenced by a body of work documenting that sensory, motor, and language behaviors are altered in the first year of life, prior to the onset of ASD symptoms [48,49]. The need to explore genetic associations early, prior to symptom onset, is well illustrated in two recent twin studies.…”
Section: Discussionmentioning
confidence: 99%